Effect of hypobaric "live high - train low" training on blood parameters in elite track cyclists - Blokker, T.; Kellenberger, K.; Müller, B.; Zenger, N.; Wehrlin, J. P. (28th Annual Congress of the European College of Sport Science, 4-7 July 2023, Paris, France, 2023)
INTRODUCTION: By combining hematological adaptations to chronic hypoxia benefits, while avoiding the hypoxia-induced reduction of maximal training intensity, "Live High - Train Low" (LHTL) has popularly grown to be a common hypoxic training practice in elite endurance sport disciplines [1]. However, despite arguably being the "gold standard" of altitude training for sea-level competition, its validity and effect, particularly within elite athletes with a high natural hemoglobin mass (Hb(mass)), remain debated [2]. Hence, the purpose of this case-study was to evaluate the effect of LHTL on blood parameters in elite track cyclists.